FACS‐Sortable Triple Emulsion Picoreactors for Screening Reactions in Biphasic Environments - Samuel Thompson; Yanrong Zhang; Zijian Yang; Lisa Nichols; Polly M. Fordyce (Advanced Materials Interfaces)
Abstract Biphasic environments can enable successful chemical reactions where any single solvent results in poor substrate solubility or poor catalyst reactivity. For screening biphasic reactions at high throughput, a platform based on microfluidic double emulsions can use widely available FACS (Fluorescence Activated Cell Sorting) machines to screen millions of picoliter reactors in a few hours. However, encapsulating biphasic reactions within double emulsions to form FACS‐sortable droplet picoreactors requires optimized solvent phases and surfactants to produce triple emulsion droplets that are stable over multi‐hour assays and compatible with desired reaction conditions. This work demonstrates such FACS‐sortable triple emulsion picoreactors with a fluorocarbon shell and biphasic octanol‐in‐water core. First, surfactants are screened to stabilize octanol‐in‐water emulsions for the picoreactor core. With these optimized conditions, stable triple emulsion picoreactors (>70% of droplets survived to 24 hr), produced protein in the biphasic core via cell‐free protein synthesis are generated, and sorted these triple emulsions based on fluorescence using a commercial FACS sorter at >100 Hz with 75–80% of droplets recovered. Finally, an in‐droplet lipase assay with a fluorogenic resorufin substrate that partitions into octanol is demonstrated. These triple emulsion picoreactors have the potential for future screening bead‐encoded catalyst libraries, including enzymes such as lipases for biofuel production.